Novel Truncating and Missense Variants in SEMA6B in Patients With Early-Onset Epilepsy - Xiaozhen, Song; Fan, Yuan; Fang, Yuan; Xiaoping, Lan; Jia, Jia; Wuhen, Xu; Xiaojun, Tang; Jun, Shen; Yucai, Chen; Hong, Zhang; Guang, He; Shengnan, Wu (Frontiers in Cell and Developmental Biology, 2021)
Progressive myoclonic epilepsy (PME) is a rare neurodegenerative disease, characterized by myoclonic seizures and tonic clonic seizures, with genetical and phenotypical heterogeneity. The semaphorin 6B (SEMA6B) gene has been recently reported a causal gene of PME. Independent studies are warranted to further support these findings. Here we report that one nonsense variant in NM_032108.3 exon17 c.2056C>T (p.Gln686*) and one missense variant in exon14 c.1483G>T (p.Gly495Trp) of SEMA6B, both occurring de novo, underlie early-onset epilepsy with variable severity and different response to treatment in two patients. In vitro analyses have demonstrated the nonsense variant, p.Gln686*, results in a truncated protein with remarkably increased expression compared to that of wild type. The truncated protein presented more homogeneous and failed to locate in the plasma membrane. The missense variant p.Gly495Trp affects evolutionarily conserved amino acid and is located in sema domain, a key functional domain of SEMA6B. It was predicted to perturb SEMA6B function by altering tertiary structure of mutant protein although neither change of protein length and expression nor difference of cellular distribution was observed. Co-immunoprecipitation studies has demonstrated both variants influence protein binding of SEMA6B and PlxnA2 with varying degrees. Our results provide further evidence to support the initial findings of SEMA6B being causal to epilepsy and indicate mediating Semaphorin/Plexin signaling is the potential mechanism of the SEMA6B-related disease.